Outcome of treatment of OPC poisoning patients with atropine or atropine plus pralidoxime - Kamal, SM; Akhter, Shamima; Ahmed, Sk Farid Uddin; Chowdhury, Poritosh Kumar; Rashid, AKM Mamunur; Islam, Md Nazrul (Bangladesh Medical Journal Khulna, 2018)
Background: Organophosphorus compound (OPC) poisoning is common in Bangladesh and management facility is not adequate in most hospitals. Both inj. Atropine and inj. Pralidoxime is used as antidote for the management of OPC poisoning, although there is controversy regarding benefit of inj. Pralidoxime. Objective: This randomised clinical trial was conducted to compare the outcome of OPC poisoning patients treated by inj. Atropine along with supportive measures and by inj. Atropine plus inj. Pralidoxime along with supportive measures . This study also evaluated the clinical profile of OPC poisoning patients. Methods: A total number of 109 patients, admitted in medicine ward in Khulna medical college hospital during one year period were included in this randomised clinical trial. The patients were divided into two groups according to alternate day of admission in the medicine wards. Forty nine patients of group A was treated by inj. atropine only along with other supportive measures required and group B of 60 patients was treated by inj. atropine plus inj. pralidoxime along with supportive measures. Results: 49 patients of group A was treated with atropine alone and 60 patients in group B was treated with atropine plus pralidoxime. Death rate was 14.28% in atropine treated group and 16.66% in atropine plus pralidoxime treated group (p=0.733). The difference in death rate is not statistically significant. Four (8.18%) patients from atropine treated group and 4 (6.67%) patients from pralidoxime intervention group developed respiratory failure and ventilatory support was given in ICU. These 8 patients recovered. But this difference in development of respiratory failure is not statistically significant (p=0.766). The difference of death rate between male and female (12.5% Vs 18.87%) is not also significant (p=0.360). Conclusion: This study reveals that pralidoxime provides no better outcome in the management of OPC poisoning patients. Bang Med J (Khulna) 2017; 50 : 3-7